Inclusive Geography Teaching—Basics, Perspectives and Guidelines - Winklmaier, Ann-Sophie; Schubert, Jan Christoph (Journal of Geography Education, 2024)
In the context of inclusive education, geography teaching should ensure that all students can actively engage in and benefit from geographic learning. However, the discussion around how to effectively teach geography inclusively, particularly for students with special educational needs, is still in its early stages. This article aims to clarify key principles and terminology related to inclusive geography teaching and to integrate concepts from the field of inclusive pedagogy with geography education. Building on this foundation, the article proposes guidelines for inclusive geography teaching, which are designed to stimulate further discussion, be empirically tested, and refined over time.